Accounting for the Material Stock of Nations. (10th April 2014) - Fishman, Tomer; Schandl, Heinz; Tanikawa, Hiroki; Walker, Paul; Krausmann, Fridolin
Summary National material stock (MS) accounts have been a neglected field of analysis in industrial ecology, possibly because of the difficulty in establishing such accounts. In this research, we propose a novel method to model national MS based on historical material flow data. This enables us to avoid the laborious data work involved with bottom‐up accounts for stocks and to arrive at plausible levels of stock accumulation for nations. We apply the method for the United States and Japan to establish a proof of concept for two very different cases of industrial development. Looking at a period of 75 years (1930–2005), we find that per capita MS has been much higher in the United States for the entire period, but that Japan has experienced much higher growth rates throughout, in line with Japan's late industrial development. By 2005, however, both Japan and the United States arrive at a very similar level of national MS of 310 to 375 tonnes per capita, respectively. This research provides new insight into the relationship between MS and flows in national economies and enables us to extend the debate about material efficiency from a narrow perspective of throughput to a broader perspective of stocks.